The influence of dietary supplementation with ginger ethanol extract on laying hens’ production performance, antioxidant capacity, and gut microbiota - Jin, Sanjun; Shi, Jiajia; Zhao, Mixue; Liu, Xinhe; Yang, Kaige; Shang, Enci; Wang, Ping; Liu, Chaoqi; Wang, Lijun; Li, Xinxin; Yin, Qingqiang; Yue, Zhiguang; et al. (Frontiers in Veterinary Science, 2025)
This study aimed to investigate the effects of ginger ethanol extract (GEE) on the production performance, egg quality, serum biochemistry, antioxidant capacity, and gut microbiota of Dawu Golden Phoenix laying hens. The study included 288 Dawu Golden Phoenix laying hens, aged 44 weeks, which were randomly divided into four groups: CON (basal diet), GEE 200 (basal diet + 200 mg kg−1 GEE), GEE 400 (basal diet + 400 mg kg−1 GEE), and GEE 600 (basal diet + 600 mg kg−1 GEE). The results demonstrated that dietary GEE significantly increased apparent ether extract (EE) digestibility (p < 0.05) compared to the basal diet. Hens that were fed GEE diets exhibited an improved feed-to-egg ratio (FCR) and increased levels of serum total protein (TP) and high-density lipoprotein cholesterol (HDL-C) (p < 0.05), along with reduced levels of serum total triglycerides (TG) and low-density lipoprotein cholesterol (LDL-C) (p < 0.05). Furthermore, dietary GEE (600 mg kg−1) significantly increased serum antioxidant capacity and estradiol (E2) levels (p < 0.05). No significant differences were observed in alpha and beta diversity across the groups, except for the Chao index (p < 0.05). Bacteroidota and Firmicutes predominated at the phylum level, while Bacteroides emerged as the dominant genus. The Firmicutes-to-Bacteroidota ratio tended to increase in the GEE400 and GEE600 groups. At the genus level, hens that were fed 600 mg kg−1 of GEE showed significantly higher abundances of Faecalibacterium and Rikenellaceae_RC9_gut_group, but lower abundances of Bacteroides and unclassified_o_Bacteroidales compared to the CON group (p < 0.05). Correlation analysis revealed that Lactobacillus and Faecalibacterium were positively correlated with antioxidant capacity, indicating that GEE improved antioxidant status by increasing the relative abundances of beneficial intestinal probiotics. The paper concludes with a discussion that GEE supplementation improved animal production by reducing the FCR value and enhancing apparent EE digestibility, while modulating serum biochemical parameters. It also enhanced the antioxidant function by regulating gut microbiota. Therefore, the optimal addition of GEE as a feed additive for laying hens is 600 mg kg−1.